Revitalisasi Kearifan Lokal Naskah-naskah Primbon Koleksi Masyarakat Indramayu - Nurhata Nurhata (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2018)
The primbon manuscript has concrete implications for social life, both concerning individual needs and collective needs of society. Various problems faced by the community some time ago, referring to the primbon as a reference, because the truth has been tested, like a roadmap that will direct someone to a specific goal. The use of primbon is generally through